Ola Andersen on Professional Learning for Culturally Nourishing Professional Learning: Delivery and Outcomes of Workshops - Andersen, Ola (2022)
Ola Andersen is a community based researcher on the SSHRC-funded project "Professional Learning for Culturally Nourishing Pedagogies in Nunatsiavut Area Schools". In this video, she describes the delivery of online workshops for Nunatsiavut educators, and their outcomes.